Computer model of information behavior to study information security professionals - Ohtoshi, Paulo Hideo; Duque, Cláudio Gottschalg (Brazilian Journal of Information Science, 2018)
In this paper, we propose a computer model of information behavior to study information security professionals and an architecture, which mimics the way our brain learns new concepts to simulate this behavior computationally. Used to represent and describe any domain of knowledge, we may use ontologies to study the human information behavior and show some of the concepts and relation-ships involved in this field of knowledge. A deep knowledge of the core concepts underpinning this field can provide us with a solid basis for constructing a model. We can also use computer-programming tools not only to capture the ideas that make up this field of knowledge, but can also simulate the human information behavior. The use of computers also allows us to crawl data over the Internet and process large amounts of them in order to find patterns with some specific characteristics. In the paper, we also present the current state of this research and challenges of the model.